2012
DOI: 10.1007/s00011-011-0425-3
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 receptors BLT1 and BLT2 are involved in interleukin-8 production in human neutrophils induced by Trichomonas vaginalis-derived secretory products

Abstract: Our results suggest that LTB(4) receptors BLT1 and BLT2 are involved in IL-8 production in neutrophils induced by T. vaginalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 42 publications
0
29
0
4
Order By: Relevance
“…В log-фазе роста проводили сбор Trichomonas vaginalis с последующей однократной промывкой сбалансированным солевым раствором Хенкса (HBSS) (NaCl 2. Отмытые T. vaginalis ресуспендировали в 1,0 мл HBSS (до концентрации 1,0·10 7 /мл) и инкубировали 60 мин при 37 °С (для максимального накопления продуктов секреции патогена) [13,15,16].…”
Section: материал и методыunclassified
See 2 more Smart Citations
“…В log-фазе роста проводили сбор Trichomonas vaginalis с последующей однократной промывкой сбалансированным солевым раствором Хенкса (HBSS) (NaCl 2. Отмытые T. vaginalis ресуспендировали в 1,0 мл HBSS (до концентрации 1,0·10 7 /мл) и инкубировали 60 мин при 37 °С (для максимального накопления продуктов секреции патогена) [13,15,16].…”
Section: материал и методыunclassified
“…После инкубации супернатант культуральной среды центрифугировали 10 мин при 10 000 g, а затем пропускали через фильтр (диаметр 0,22 мкм) [13].…”
Section: материал и методыunclassified
See 1 more Smart Citation
“…In previous studies, we found that TvSP or T. vaginalis-derived LTB 4 can induce exocytosis and interleukin-8 (IL-8) production in human granulocytes (34)(35)(36)(37). TvSP induced upregulation of CD63 expression and reactive oxygen species (ROS) generation in HMC-1 cells via activation of mitogen-activated protein kinases (MAPKs) (35).…”
mentioning
confidence: 99%
“…T. vaginalis-derived LTB 4 can induce HMC-1 cells to release IL-8 via LTB 4 receptor (BLT)-dependent activation of NF-B and CREB (21). Similarly, in neutrophils, NF-B and CREB were involved in IL-8 production induced by TvSP in BLT-dependent signaling (36,37). More recently, we showed that LTB 4 -stimulated eosinophils showed upregulation of CD63, a marker of exocytosis, via surface translocation of BLT1 in a nicotinamide adenine dinucleotide phosphate oxidase 2 (NOX2)-derived ROS-dependent manner (34).…”
mentioning
confidence: 99%